Prevalência de incontinência urinária e disfunção muscular do assoalho pélvico em primíparas dois anos após parto cesárea: Estudo transversal - Pascon Barbosa, Angélica Mércia [UNESP]; Marini, Gabriela [UNESP]; Piculo, Fernanda [UNESP]; Rudge, Cibele Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (FapUNIFESP (SciELO), 2013)
CONTEXT AND OBJECTIVE: There is uncertainty in the literature regarding the theory that obstetric events and pelvic floor injuries give rise to lower risk of subsequent urinary incontinence among women delivering via cesarean section than among women delivering vaginally. The objective of this study was to assess the two-year postpartum prevalence of urinary incontinence and pelvic floor muscle dysfunction and the factors responsible for them. DESIGN AND SETTING: Cross-sectional study, conducted in a public university. METHODS: 220 women who had undergone elective cesarean section or vaginal childbirth two years earlier were selected. Their urinary incontinence symptoms were investigated, and their pelvic floor muscle dysfunction was assessed using digital palpation and a perineometer. RESULTS: The two-year urinary incontinence prevalences following vaginal childbirth and cesarean section were 17% and 18.9%, respectively. The only risk factor for pelvic floor muscle dysfunction was weight gain during pregnancy. Body mass index less than 25 kg/m2 and normal pelvic floor muscle function protected against urinary incontinence. Gestational urinary incontinence increased the risk of two-year postpartum urinary incontinence. CONCLUSION: Gestational urinary incontinence was a crucial precursor of postpartum urinary incontinence. Weight gain during pregnancy increased the subsequent risk of pelvic floor muscle dysfunction, and elective cesarean section did not prevent urinary incontinence.
Prevalence of urinary incontinence and pelvic floor muscle dysfunction in primiparae two years after cesarean section: Cross-sectional study
Keywords: Cesarean section; Pelvic floor; Postpartum period; Pregnancy; Urinary incontinence; adult; body mass; cesarean section; cross-sectional study; female; gynecologic disease; human; major clinical study; pelvic floor muscle dysfunction; postoperative period; prevalence; primipara; puerperium; risk factor; urine incontinence; vaginal delivery; weight gain